Chemical Content and Sensory Characteristics of Herbal Chicken Essence from Indonesia - Kusumaningrum, Indah; Sulaeman, Ahmad; Palupi, Eny; Sinaga, Tiurma; Wibawan, I Wayan Teguh (Jurnal Gizi dan Pangan, 2023)
The purpose was to determine the chemical content (water, protein, fat, ash, and carbohydrate) and sensory characteristics of Herbal Chicken Essence (HCE), a functional drink containing chilcken extract, from Indonesia. The experimental design was factorial and completely randomized with two replicates. There are four formulas in this study, namely F1 (broiler chicken and coconut sugar), F2 (broiler chicken and coconut sugar), F3 (IPB D1 chicken and palm sugar), and F4 (IPB D1 chicken and coconut sugar). The chemical content data were analyzed using a two-way ANOVA. Panelists used in the sensory tests included 30 participants. There was a significant effect (p<0.05) of chicken and sugar substitution on water, ash, protein, and carbohydrate contents. Formula 2 (broiler chicken and coconut sugar) is the most preferred in almost all sensory attributes (aroma, taste, mouthfeel, aftertaste, and overall acceptance) because the sour taste found in coconut sugar is able to suppress the fishy taste found in HCE. The substitution of the chicken breed and sugar in the HCE formulations affected the chemical content and sensory characteristics